Efecto del coxsackievirus B3 en la respuesta inflamatoria de los neutrófilos - Juchazara Choqueticlla, Rosario (2022)
Coxsackievirus B3 (CVB3) is a globally prevalent enterovirus of the Picornaviridae family that is frequently associated with viral myocarditis (VM). The mechanism underlying the pathogenesis of VM is not well established. Neutrophils, as first-responders, may be key cells in determining viral disease outcome and even though neutrophils have been ascribed to have a relevant role in early cardiac inflammation, their precise role in CVB3 infection has not yet been evaluated.\nIn this study, we aimed to determine if the interaction of human neutrophils with CVB3 could lead to viral replication, modulation of neutrophil survival and activation of neutrophils.\nOur results showed that CVB3 interacted with but did not replicate in human neutrophils. Neutrophils recognized CVB3 mainly through endosomal TLR-8, and infection triggered NF-?B activation. Virus internalization resulted in an increased cell survival, an up-regulation of CD11b expression, an adhesion to fibronectin, and the secretion of pro-inflammatory cytokines IL-6, IL-1?, TNF-?, and chemokine IL-8. Supernatants from infected neutrophils exerted chemotactic activity mediated by IL-8. The infected neutrophils released myeloperoxidase and triggered neutrophil extracellular traps formation, which was further increased in the presence of TNF-?. Our results indicate that CVB3 triggers a marked activation of neutrophils and a pro-inflammatory response. These findings can be the basis for new therapeutic strategies against infection with CVB3.